A Language of Song: Journeys in the Musical World of the African Diaspora. Samuel Charters. 2009. London and Durham, NC: Duke University Press. 59 photos, index, 368pp. - Watkins, Lee (International Library of African Music, 2014)
pages: 147-148
Keywords: African Music